Mental Imagery and Brain Regulation—New Links Between Psychotherapy and Neuroscience - Skottnik, Leon; Linden, David E. J. (Frontiers in Psychiatry, 2019)
Mental imagery is a promising tool and mechanism of psychological interventions, particularly for mood and anxiety disorders. In parallel developments, neuromodulation techniques have shown promise as add-on therapies in psychiatry, particularly non-invasive brain stimulation for depression. However, these techniques have not yet been combined in a systematic manner. One novel technology that may be able to achieve this is neurofeedback, which entails the self-regulation of activation in specific brain areas or networks (or the self-modulation of distributed activation patterns) by the patients themselves, through real-time feedback of brain activation (for example from functional magnetic resonance imaging). One of the key mechanisms by which patients learn such self-regulation is mental imagery. Here we will first review the main mental imagery approaches in psychotherapy and the implicated brain networks. We will then discuss how these networks can be targeted with neuromodulation (non-invasive or invasive brain stimulation or neurofeedback). We will review the clinical evidence for neurofeedback and discuss possible ways of enhancing it through systematic combination with psychological interventions, with a focus on depression, anxiety disorders and addiction. The overarching aim of this perspective paper will be to open a debate on new ways of developing neuro-psychotherapies.